2022
DOI: 10.1007/s13402-022-00695-4
|View full text |Cite|
|
Sign up to set email alerts
|

YAP1 acts as a negative regulator of pro-tumor TAZ expression in esophageal squamous cell carcinoma

Abstract: Purpose Although YAP1 and TAZ are believed to be equivalent downstream effectors of the Hippo pathway, differential expression of YAP1 or TAZ suggests distinct functions during cancer progression. The exact role of YAP1 and TAZ in esophageal cancer, the 6th leading cancer-related mortality in the world, remains elusive. Methods Following single or double manipulation of YAP1 or TAZ expression, we subjected these manipulated cells to proliferation, migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In different conditions, YAP can function as both an oncogene and a tumor suppressor gene. There is a report suggesting that YAP functions as a tumor suppressor, whereas TAZ plays a role in promoting tumor growth in ESCC [ 54 ]. However, our data and other studies from different teams do not support this view.…”
Section: Discussionmentioning
confidence: 99%
“…In different conditions, YAP can function as both an oncogene and a tumor suppressor gene. There is a report suggesting that YAP functions as a tumor suppressor, whereas TAZ plays a role in promoting tumor growth in ESCC [ 54 ]. However, our data and other studies from different teams do not support this view.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that YAP1 is lessened in esophageal squamous cell carcinoma and medullary thyroid carcinoma. [41][42][43] drugs in FLT3-ITD + AML cells and docetaxel resistance in prostate cancer. 44,45 In our study, we confirmed that miR-375-3p targets YAP1.…”
Section: Discussionmentioning
confidence: 99%
“…In general, most of the molecular functions of YAP and TAZ overlap. However, several articles demonstrated that YAP and TAZ have distinct functions [25,[44][45][46]. For instance, YAP and TAZ knockout mice exhibit different phenotypes.…”
Section: Discussionmentioning
confidence: 99%